Correlation of p53 and KI-67 expression with grade and subtype of ependymoma - Lakshmi P Manasa; M S Uppin; C Sundaram (Wolters Kluwer Medknow Publications, 2012)
Introduction: The morphological criteria for grading ependymomas were always felt subjective. Recently some studies have showed that Ki-67 and p53 immunolabeling are important prognostic markers in ependymomas. Materials and Methods: All the cases of ependymomas diagnosed from 2005 to 2010 were graded according to WHO classification for central nervous system (CNS) tumors 2007. Two tissue microarray (TMA) blocks were prepared. Immunohistochemical analysis with glial fibrillary acidic protein (GFAP), epithelial membrane antigen (EMA), Ki-67 and p53 was performed. The difference in expression of p53 and Ki-67 in various tumor grades and subtypes was evaluated using Student's t test. Results: There were 54 cases with a M: F ratio of 1.34 : 1, age ranging from 7 years to 65 years (mean 29.35 years). There were 33 intracranial and 21 spinal cases. There were 9 grade I ependymomas, 32 grade II ependymomas and 13 grade III ependymomas. GFAP immunopositivity was seen in all the cases and EMA was positive in 49% cases. The mean p53 indices were higher in grade III and grade II tumors (26.26% and 26.08%) as compared to subependymomas (7.25%). But these values did not show statistical significance (P = 0.2). The Ki-67 labeling index increased from grade I to grade III tumors. The difference was highly significant between grade II and grade III (0.5% vs. 2.75, P = 0.016). Conclusion: Ki-67 labeling index correlates with grade of ependymoma (P = 0.016). There is no correlation between p53 expression and grade of ependymomas.